2009
DOI: 10.1002/jmv.21406
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of cellular RNA‐binding proteins in HPV‐induced neoplasia and cervical cancer

Abstract: The expression profile of a panel of RNA-binding proteins (heterogeneous ribonucleoprotein (hnRNP) A1, hnRNP C1/C2, hnRNP H, hnRNP I, ASF/SF2, SR proteins, HuR and U2AF(65)) and markers of differentiation, proliferation and neoplasia (cytokeratin (CK) 13, CK-14, proliferating cell nuclear antigen (PCNA), Syndecan-1 and p16INK4a) were analyzed in 50 formalin fixed paraffin embedded cervical tissues using immunohistochemistry. The samples included histologically normal cervical epithelium, human papillomavirus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
57
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 50 publications
(59 reference statements)
6
57
1
Order By: Relevance
“…Of the early HPV-16 mRNAs that are selectively stimulated by high levels of ASF/SF2, there is an overrepresentation of mRNAs that express viral cell growthstimulatory proteins, including E5, E6, and E7. This deduction fits well with the previously observed high expression levels of ASF/SF2 in high-grade cervical lesions and cervical cancers (7). It was previously reported that HPV-16 E2 enhances ASF/ SF2 expression by transcriptional activation of the ASF/SF2 promoter (19).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of the early HPV-16 mRNAs that are selectively stimulated by high levels of ASF/SF2, there is an overrepresentation of mRNAs that express viral cell growthstimulatory proteins, including E5, E6, and E7. This deduction fits well with the previously observed high expression levels of ASF/SF2 in high-grade cervical lesions and cervical cancers (7). It was previously reported that HPV-16 E2 enhances ASF/ SF2 expression by transcriptional activation of the ASF/SF2 promoter (19).…”
Section: Discussionsupporting
confidence: 92%
“…We have shown that a number of RNA-binding proteins, including splicing factor ASF/SF2, are overexpressed in cervical cancers (7). As a matter of fact, ASF/SF2 expression increased with the grade of severity of the cervical lesion induced by HPV, as did expression of most RNA binding proteins (7). Relatively few cells expressed ASF/SF2 in normal HPV-negative cervical epithelium (7).…”
Section: Discussionmentioning
confidence: 99%
“…Using cell line models of epithelial differentiation and HPV infection and backed up by data from virus-infected patient tissue, we and others demonstrated that SRSF1 (SF2/ASF), SRSF2 (SC35), and SRSF3 (SRp20) are specifically upregulated in HPVinfected, differentiated epithelial cells (24,25,31,32). For SRSF1, we showed previously that HPV16 E2 controlled the promoter of the SRSF1 gene by interacting within a region from nt Ϫ565 to nt Ϫ363 with respect to the transcription initiation site (this was originally cited as nt Ϫ689 to nt Ϫ482 in our previous paper [25] according to the numbering of a previously sequenced version of the SRSF1 promoter).…”
Section: Resultsmentioning
confidence: 98%
“…Apart from RNA processing-related functions, SR proteins have also been shown to be involved in chromatin remodelling, transcriptional regulation, genome stability maintenance, nucleolar stress, cell cycle progression, apoptosis control, and protein sumoylation (15)(16)(17)(18)(19)(20). Unsurprisingly, due to their diverse functions, many SR proteins are overexpressed in a range of tumors (21)(22)(23)(24)(25). Importantly, SRSF1 (ASF/SF2), SRSF3 (SRp20), and SRSF9 (SRp30c) have been shown to possess oncogenic properties (22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%
“…Unsurprisingly, due to their diverse functions, many SR proteins are overexpressed in a range of tumors (21)(22)(23)(24)(25). Importantly, SRSF1 (ASF/SF2), SRSF3 (SRp20), and SRSF9 (SRp30c) have been shown to possess oncogenic properties (22)(23)(24)(25)(26)(27)(28)(29)(30)(31). Increased SRSF levels can result in the production of alternatively spliced RNA isoforms encoding key antiapoptotic, cell proliferation, and epithelial-mesenchymal transition (EMT)-inducing proteins (18).…”
mentioning
confidence: 99%